PENERAPAN TSAWAB W ‘IQAB DALAM MEMBANGUN SIKAP DISIPLIN SISWA DI PONDOK PESANTREN DARUSSALAM - Muhammad Julfi (Universitas Muhammadiyah Surabaya, 2022)
Islamic education is a process of developing the creative potential of students to become human beings of faith, piety, virtuous and have a high work ethic. All of them are evidence that Islamic education has experienced a satisfactory development, including educational tools or educational methods. Tsawab W'Iqab is an educational tool that is still applied to this day even though its existence is often misunderstood for guardians of students and is not infrequently misused for educators. This research was conducted using qualitative field research at Darussalam, Al-Falah and Yasin Islamic boarding schools. The subjects in this study were teachers and caregivers who had more authority over the application of tswab w'iqab at Islamic boarding schools in Darussalam, al-falah and yasin, as well as students who had received tswab w'iqab. Meanwhile, the object of this research is the way in which teachers and caregivers apply when there are students who receive tswab w'iqab and the form of tswab w'iqab that they do when applying tswab w'iqab at Islamic Boarding Schools Darussalam. Then the field data was extracted through interviews, observations, and documentation. The results showed that the application of tswab in building student discipline at the Islamic boarding school was by giving appreciation in the form of grades, trophies, certificates and scholarships to hadramaut Yemen. While the iqab given to students who violate the discipline of Islamic boarding schools in the form of restitution, deprivation, and physical punishments.Â Keywords: Application; Tsawab w'Iqab; Student Discipline; Islamic Boarding School Â Â